EMPOWERING ENGLISH LITERACY THROUGH READING CORNERS AND INSTITUTIONAL BRANDING: - Febriana, Firnanda; Dewi, Angelicha Dwi Warsita (International Journal of Community Service in Language, Literature, Culture, and Their Teaching, 2025)
This community service program at Favourite Education Centre (FEC) Situbondo aimed to address two critical challenges commonly faced by non-formal educational institutions: the lack of English literacy resources and limited institutional visibility. The initiative focused on establishing a Reading Corner to promote independent reading habits and enhance students’ English literacy, alongside developing and distributing promotional brochures to increase public awareness and institutional outreach. Guided by Social Literacy Theory and Constructivist Learning Theory, the program was implemented through a four-stage process: needs identification, program design, implementation, and evaluation. The results showed a significant increase in student engagement with English texts and positive community responses to the brochure. This integrated approach proves that strategic and context-based interventions can effectively support language learning and institutional development in non-formal education settings.